Bahasa Inggris - Hutapea, Risnawati; Abdurrahman, Abdurrahman; Anggreini, Anggreini; Suyatna, Agus (EduFisika: Jurnal Pendidikan Fisika, 2026)
One of the important competency that students need to have in the 21st century is creative problem solving ability. Preliminary study results indicate that students creative problem solving ability have not been optimally trained in the learning process. This study aims to determine the effectiveness of the PBL model integrated STEM-EDP with deep learning principles in improving students' creative problem-solving abilities on the topic of alternative energy. The research sample was taken using a purposive sampling technique, consisting of class X-E1 with 35 students and class X-E2 with 36 students at SMAN 5 Bandar Lampung. The method used was quasi-experimental with a non equivalent control group design. The data collection technique used was a test technique in the form of pretest and posttest question sheet consisting of the three essay questions. The results showed an improvement in creative problem solving ability, with an average N-gain of the experimental class of 0,61 (moderate category), higher than the control class which was 0,40 (moderate category). The results of the independent sample t-test and ANCOVA showed a Sig. (2-tailed) value of 0,000 < 0,05, and an effect size value of 0,406 (large category), which means that the PBL model integrated STEM-EDP with deep learning principles is effective in improving the creative problem solving ability of high school students, particularly on the topic of alternative energy.